2020
DOI: 10.1155/2020/7145656
|View full text |Cite
|
Sign up to set email alerts
|

Galactose-Induced Skin Aging: The Role of Oxidative Stress

Abstract: Skin aging has been associated with a higher dietary intake of carbohydrates, particularly glucose and galactose. In fact, the carbohydrates are capable of damaging the skin’s vital components through nonenzymatic glycation, the covalent attachment of sugar to a protein, and subsequent production of advanced glycation end products (AGEs). This review is focused on the role of D-galactose in the development of skin aging and its relation to oxidative stress. The interest in this problem was dictated by recent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 150 publications
(253 reference statements)
1
53
0
1
Order By: Relevance
“…These results are similar to what previously reported by our group on human erythrocytes exposed in vitro to H 2 O 2 [ 27 ]. Recent scientific evidences have reported that d- Gal accumulation induces oxidative stress, cell senescence and cytotoxicity [ 61 ]. In this regard, B3p functions, being crucial in the systemic homeostasis maintenance and affected by oxidative stress, could be correlated to oxidative stress-induced alterations during galactosemia.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to what previously reported by our group on human erythrocytes exposed in vitro to H 2 O 2 [ 27 ]. Recent scientific evidences have reported that d- Gal accumulation induces oxidative stress, cell senescence and cytotoxicity [ 61 ]. In this regard, B3p functions, being crucial in the systemic homeostasis maintenance and affected by oxidative stress, could be correlated to oxidative stress-induced alterations during galactosemia.…”
Section: Discussionmentioning
confidence: 99%
“…Galactose is a physiological nutrient that is chemically a reducing carbohydrate. It can be combining with glucose and form the disaccharide lactose [50,51]. Xylose or wood sugar has antifungal and antibacterial properties.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme deficiency in this pathway results in a disease called galactosemia [ 54 , 55 , 56 ]. Previous studies in humans showed that phosphorus in the RBCs and plasma may be decreased due to accumulation of gal-1-P in the cells [ 57 , 58 , 59 , 60 ]. In the D-gal model, a high level of galactose phosphorylation may be the cause of a decrease in the phosphorus fraction.…”
Section: Discussionmentioning
confidence: 99%